REDUCING INFANT AND UNDER-5 MORTALITY RATE THROUGH GOVERNMENT HEALTH EXPENDITURE: A SYSTEMATIC REVIEW - Alissa Sita Pertiwi; Amal Chalik Sjaaf (Indonesian Journal of Health Administration, 2022)
Background: Although it has been globally reported that IMR and U5MR continue to decline every year, the rate disparities between urban and rural areas are still evident in various countries. The government is presumed to carry out efforts to reduce this disparity, such as by allocating the government’s health expenditure. Aims: This study systematically identifies the effectiveness, best practices, and positive impacts of government health expenditure allocation for IMR and U5MR, specifically in rural areas. Methods: This systematic review study was conducted using the PICOS method to analyse data that were obtained from 3 online databases. Results: The government health expenditure could reduce the gap in mortality rate indicators between urban and rural areas. Programs specifically proposed for rural communities can help decrease the gap between urban-rural IMR and U5MR. The effectiveness of government health expenditure to reduce mortality rates was strongly influenced by various factors, including supporting policies, field implementation in regions, and the collaboration between the central and local governments. Conclusion: The local government plays a definitely crucial role in the implementation of the health program to ensure that the central government executes the program effectively in order to reduce IMR and U5MR in rural areas.